Penta Helix Model Tourism Development In The City of Palembang - Rina Herawati, Augustin; Larasati Setianingsih, Endang; Hariani, Dyah (Green Publisher Indonesia, 2022)
This research is a literature study on the penta helix model. This study aims to analyze the penta helix model of tourism development in the city of Palembang. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study conclude that there are five important things or indicators that need to be considered in using this analysis. These five lines are, among others, shortened to ABCGM. The results of the pentahelix analysis on tourism in the city of Palembang, as for the roles and duties of each line/field that synergize with one another, among others, Academics in the Penta Helix model act as drafters, the private sector in the Penta Helix model acts as an enabler, Community in the Penta Helix model Penta Helix acts as an accelerator, the government must act as a regulator as well as a controller, the media must be able to act as an expander.